METODE LATIHAN KETERAMPILAN DALAM MENINGKATKAN PERKEMBANGAN MOTORIK ANAK - Asriyanti Panda Banjal; Tantri Yulia; Eni Rombe (JOURNAL of THEOLOGICAL STUDENTS, 2020)
The research objective was to determine how much the skill training method on children's motor development atDaniel Creatif School Semarang. The results of the first hypothesis, which were proposed in this study, namely:it is suspected that the skills training method is in the moderate category or 60% is not accepted.The secondhypothesis proposed in this study is that it is suspected that children's motor development is in the moderatecategory or 60% is not accepted. The third hypothesis is that the level of influence of skills training methods on children's motor development is in the very high category and is not accepted. Because the correlationcoefficient value obtained is 866a, it is in the very high category in the correlation coefficient interpretation table.